The Role of Organization Collage Student a Study Program to Build Leadership Character Candidate Chemistry Teacher - Leony Sanga Lamsari Purba; Elisa Natalia Sibarani (Jurnal Pendidikan Kimia (JPKim), 2017)
Abstract: The development of social media into today's style of life. The decline in the child's desire to follow communities a result of the use of social media affect the formation of character in children. Character education is a very good effort from all of people who develop education. Science briefing will children with good character is the responsibility of all of people involved in education for the future of dignity. Teachers is an asset in the world of education should have good prospects in education which is not a crisis of character. Organization is a place for prospective teachers to build character. This study aims to describe the role of student organization of study program in developing the leadership character of prospective educators of Chemistry Christian University of Indonesia. The focus in this research is the role of organization of student set of study program in shaping the leadership character of prospective educator. In this research, qualitative approach and case study research design is used to collect data by technique (1) in-depth interview, (2) nonparticipant observation, (3) documentation study. Data analysis techniques use data reduction, data presentation, verification or conclusion. The result of this research is the role of organization of student set of study program in shaping the leadership character of prospective educator by giving courage, integrity, good sense of humor and maturity which is 96.5%, 93,75%, 93,75% and 91, 25% on prospective educators. So, the students are expected to join the organization of student group of study program is effort done in shaping the leadership character of prospective educator of Chemistry Christian University of Indonesia.Keywords: character, chemistry, educators